2012
DOI: 10.1111/j.1460-9592.2012.03816.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic analysis of the anatomical relationships between vertebral arteries and internal jugular veins in children

Abstract: BackgroundAccidental puncture of the vertebral arteries (VAs) can occur through the internal jugular veins (IJVs) during central venous catheterization (CVC). We evaluated the anatomic relation of the VAs to the IJVs in children undergoing IJV cannulation.MethodsFifty-five patients were placed in the supine position under general anesthesia. The right IJV, common carotid artery (CCA), and VA were described with an ultrasound probe perpendicular to all planes of the skin at the mid-portion between the supraster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
1
10
2
Order By: Relevance
“…In our cohort with a similar body weight, the relative size of the VA to the IJV was greater (22.4% and 40.2% on the right and left sides, respectively, at the cricoid level) and the distance between the VA and IJV was greater (mean 6.0 mm in group 1) compared to those in the previous study. In another study performed in children with a mean age of 20.3 months, the distance between the VA and IJV was 4.6 (1.8) mm on the right side when evaluated using ultrasonography . The differences in the results between our study and these previous studies may have occurred because of the following reasons.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In our cohort with a similar body weight, the relative size of the VA to the IJV was greater (22.4% and 40.2% on the right and left sides, respectively, at the cricoid level) and the distance between the VA and IJV was greater (mean 6.0 mm in group 1) compared to those in the previous study. In another study performed in children with a mean age of 20.3 months, the distance between the VA and IJV was 4.6 (1.8) mm on the right side when evaluated using ultrasonography . The differences in the results between our study and these previous studies may have occurred because of the following reasons.…”
Section: Discussioncontrasting
confidence: 75%
“…Overlapping between the VA and IJV can contribute to the risk of inadvertent VA puncture during IJV catheterization. According to previous studies, about 40%‐82% of pediatric patients showed full or partial overlap between the VA and IJV on the right side . In our study involving chest CT in children at the neutral position, full or partial overlap was observed in 52%‐78% of children.…”
Section: Discussionsupporting
confidence: 54%
“…Several studies examined the anatomical relationship between CCA and IJV [8][9][10][11][12], but there are only a few between IJV and VA [13]. In the present study, VA was identified in all children at the level of the cricoid cartilage.…”
Section: Discussionmentioning
confidence: 96%
“…An accidental vertebral arterial puncture was reported during central venous catheterization in a child undergoing ventricular septal defect repair . Vertebral arteries are seen behind the IJV to a certain extent . A 19.0‐mm‐long 24‐G puncture needle used in this study was advanced to a maximum depth of 9.5 or 16.0 mm, following insertion at 30 or 60 degree, respectively.…”
Section: Discussionmentioning
confidence: 99%